Cell cycle analysis of F'lac replication in Escherichia coli B/r. - Finkelstein, M (1977)
The timing and control of replication of an F'lac plasmid was investigated in two substrains of Escherichia coli B/r lac/F'lac growing at a variety of rates. The cellular content of covalently closed circular F'lac deoxyribonucleic acid and the cellular mass at the time of F'lac replication both increased as a function of growth rate. The timing of plasmid replication during the division cycle was determined by measuring the inducibility of beta-galactosidase in cells of different ages in exponentially growing cultures. At all growth rates, the rate of induced beta-galactosidase synthesis increased in a step-wise fashion during the division cycle, indicating that the F'lac plasmid replicated at a discrete time in the cycle. At growth rates greater than one doubling per h, the cell age at F'lac replication was indistinguishable from the cell age at chromosomal lac+ replication in an isogenic F- parent. The ratio of plasmids to chromosomal origins decreased from about 0.7 to 0.4 between growth rates of 1.0 to 2.5 doublings per h. These observations are all consistent with replication of F'lac at about the same time in the division cycle as replication of the homologous chromosomal region at these growth rates. This similarity in timing of replication of homologous deoxyribonucleic acid regions was not evident in slower-growing cells.